(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This study analysed the Indian Solar Power Generation research record output during 2008 – 2017 is using for different scientometric indicators. Data retrieved from SCOPUS international multidisciplinary online database using the search keywords Indian and Solar Power Generation. During the Study Period, a total number of 20,119 records have been identified. Out of which, 1,903 records are contributed in India. From the study analyzed the statistical tools such as the growth of publication in Globe and India, the percentage of sharing in Indian authors’ record, the ranking of top 20 institution and journals contributions and scientometric techniques such as AI and PEI. Analysis of document wise distribution and authorship pattern.